Pulps for Strawboards from Andropogon Contortus Linn (Kusal Grass) - Bhat, R. V.; Singh, Man Mohan (Indian Forester, 1960)
Laboratory experiments carried out on the production of strawboards from Andropogon contortus Linn (kusal grass) by the lime process are described. Suitability of tea waste and roots of panni grass (Vetiveria zizanioides) for the production of strawboards was also investigated. Strength properties of commercial strawboards were determined for getting data for such boards.